The Differential Expression Profiles of miRNA-let 7a, 7b, and 7c in Bronchoalveolar Lavage Fluid From Infants With Asthma and Airway Foreign Bodies - Hang-Hu Zhang MS; Cai-Xue Li MS; Lan-Fang Tang PhD (SAGE Publishing, 2019)
The aim of this study was to investigate the expression patterns of miRNA-let 7a, 7b, and 7c in bronchoalveolar lavage fluid in infants with asthma and airway foreign bodies. Between January 2016 and February 2017, 27 infants were included and divided into observation group (infants with asthma, n = 15) and control group (infants with airway foreign bodies, n = 12). The differential expression profiles of miRNA-let 7a, 7b, and 7c were determined by reverse transcription-polymerase chain reaction in bronchoalveolar lavage fluid (BALF) from infants of the 2 groups. The BALF was collected from infants undergoing flexible bronchoscopy. MiRNA-let 7a, 7b, and 7c increased significantly in infants from observation group as compared with control group (2.72 ± 0.48 vs 1, 8.23 ± 1.64 vs 1, 3.16 ± 0.62 vs 1, respectively). The increased expression of miRNA-let 7a, 7b, and 7c were associated with the asthma of infants.